INHIBITORY ACTIVITY OF FIVE TROPICAL PLANTS IN MALAYSIA AGAINST MEDICALLY IMPORTANT MICROORGANISMS - Yeh, S. L.; Soo, P. Y.; Teo, S. R.; Teoh Sit, K. S. N. W. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The development and spread of microbial resistance has necessitated a search for novel antimicrobial agents for treatment of infectious diseases. Thus, the present study was carried out to evaluate the potential antibacterial activity of five tropical plants against medically important bacteria (Gram positive: Bacillus cereus and Staphylococcus aureus; Gram negative: Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa) using a colorimetric broth microdilution method with resazurin as a growth indicator. The crude ethanolic extract and its various fractions (hexane, chloroform, ethyl acetate, butanol and water) of each plant were evaluated at concentrations ranging from 5 to 0.04 mg/mL using two-fold serial dilution. All the extracts and fractions tested were found to have percent activity of 40% except the ethyl acetate fraction of Artocarpus integer fruits (20%), chloroform fraction and aqueous fraction of Euphorbia heterophylla stem (both 0%). The lowest minimal inhibitory concentration (0.04 mg/mL, average of two replicates) was given by the ethyl acetate fraction of Manihot esculenta leaves against B. cereus and P. aeruginosa. In contrast, the highest total activity was recorded on the crude ethanolic extract of Citrus grandis leaves against P. aeruginosa (171.9 mL/g). Among the bacteria studied, E. coli and S. aureus were the least susceptible bacteria, with the bacterial susceptibility index (BSI) of 36.7%. In addition, this study also demonstrated the limitation of using resazurin in natural product research, as auto-reduction of this indicator occurred in some of the fractions of Spondias cytherea fruits.